Pengaruh Daya Tarik Wisata Terhadap Niat Berkunjung Ulang Melalui Kepuasan Wisatawan (Studi pada wisatawan “Kampung Warna Warni” di Kota Malang) - Cahyanti, Mega Mirasaputri (Akutansi Bisnis & Manajemen ( ABM ), 2018)
This research has several objectives: (1) Knowing the influence of tourist attraction to the satisfaction of tourists,(2) Knowing the effect of tourist satisfaction on the intention of repeated visit, and (3) Knowing the direct influence of tourist attraction to the intention of the visit of tourists in Kampung Warna Warni Kota Malan. This research method using quantitative approach with descriptive analysis method, data collecting technique by spreading questionnaires to 100 respondents at tourist sites and hypothesis testing method using path analysis. The result shows that: (1) The tourist attraction has a significant effect on the satisfaction of the tourists (H1 accepted), (2) The satisfaction of tourists has a significant influence on the intention of the tourist visiting in Kampung Warna Warni Malang (H2 accepted), and (3) Tourist attraction has a significant direct effect on the intention of the visit of tourists in Kampung Warna Warni Malang (H3 accepted). And the results of testing Sobel show that the variable satisfaction of tourists mediate tourist attraction and intention to re-visit the Kampung Warna Warni Malang.